2010
DOI: 10.1016/j.jtcvs.2010.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic endovascular aortic repair for acute complicated type B aortic dissection: Superiority relative to conventional open surgical and medical therapy

Abstract: Thoracic endovascular aortic repair for acute complicated type B dissection is associated with superior early outcome and improved midterm survival relative to conventional therapy. Longer follow-up demonstrating survival benefit is needed before definitive conclusion can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(119 citation statements)
references
References 20 publications
5
102
0
2
Order By: Relevance
“…55,60,77,86,87 In these settings, TEVAR has shown a substantial advantage over OR in terms of early mortality.…”
Section: Endovascular Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…55,60,77,86,87 In these settings, TEVAR has shown a substantial advantage over OR in terms of early mortality.…”
Section: Endovascular Repairmentioning
confidence: 99%
“…99 Another study confirmed these findings with an in hospital mortality of 4%, 40%, and 33% in TEVAR, OR, and medically treated patients, respectively. 87 However, there is no evidence that extended coverage of the DTA is needed to restore distal perfusion.…”
Section: E8992e94mentioning
confidence: 99%
See 1 more Smart Citation
“…In a paper from the University of Pennsylvania Medical Center, the in-hospital mortality rate following endovascular repair for complicated type B AAD was only 4% than open surgical therapy (40%) and medical therapy (33%) (P=0.006). In addition, the benefit of endovascular repair has been conveyed as demonstrated by improved 5-year survival with evidence of aortic remodeling (10). Regarding type B AAD, endovascular repair is becoming popular in light of more evidence of improved early and late outcomes.…”
Section: Surgical or Medical Outcomesmentioning
confidence: 99%
“…Despite an improved surgical technique and perioperative care, the early mortality rate of conventional open repair for ruptured acute type B aortic dissection are 30 -40 % (Sachs T, et al, 2010, Zeeshan A, et al, 2010. Because clinical status of patients with rupture is already in a critical condition before surgery, a less-invasive initial treatment should be desirable, such as TEAVR.…”
Section: Ruptured Acute Type B Aortic Dissectionmentioning
confidence: 99%